Pengaruh Promosi dan Fasilitas Terhadap Keputusan Konsumen Menginap Pada Pia Hotel Pandan Kabupaten Tapanuli Tengah - Anri Hutagalung (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study examines the influence of promotion and facilities on consumers’ lodging decisions at PIA Hotel Pandan, Central Tapanuli Regency. Using a quantitative approach with associative methods, data were collected through validated and reliable questionnaires and analyzed using multiple linear regression. The results show that both promotion and facilities have a positive and significant effect on lodging decisions, both individually and simultaneously. The regression model (Y = 3.582 + 0.495X1 + 0.447X2) indicates that improvements in promotion and facilities increase consumers’ lodging decisions, with a determination coefficient of 66.3%. These findings highlight the importance of effective promotion and quality facilities in enhancing consumers’ decisions to stay at PIA Hotel Pandan.